Practice of the decision of the national procress in the 20th XX century (Journal of history, 2019)
Article is devoted to synthesis of practice of the solution of an ethnic question in Kazakhstan in the twenties. In article the history and a historiography of a problem of interethnic processes in Kazakhstan in the 20th years of the XX century are considered. Giving a retrospective assessment to the published literature on a historiography of the Soviet society, including on an historiography of the international relations, it should be noted negative impact of the party and state documents for the concept of national policy that undoubtedly led to wrong concepts and ideological dogmas. Therefore everything listed led to inadequate reflection of historical reality, tendentiousness of judgments, practice of concealing and distortions In article the main problems of a historiography of establishment of the Soviet power in the region and Sovietization of the Kazakh aul, formation of the Kazakh Autonomous SSR and the Kazakh SSR are also considered. The analysis of publications of this period showed strengthening of attention of researchers to an ethnic perspective. Changes in social-class structure of the population of Kazakhstan, social and economic transformations in the Kazakh aul and in the Russian village, the national peasantry, demographic characteristics of the population were mainly studied.